Chronic asymptomatic orchitis in dogs alters Sertoli cell number and maturation status - Rehder, Pauline; Packeiser, Eva-Maria; Körber, Hanna; Goericke-Pesch, Sandra (Frontiers in Veterinary Science, 2025)
Infertility due to non-obstructive azoospermia is a common diagnosis in infertile male dogs. Chronic asymptomatic orchitis (CAO) has been postulated as a significant cause of non-obstructive azoospermia in acquired male canine infertility. Despite severe microenvironmental changes, some resilient spermatogonial stem cells persist in CAO-affected testes. As Sertoli cells play an essential role in spermatogenesis and the testicular micromilieu, they represent a new target for CAO potential treatment and consequently deserve further investigation. To investigate Sertoli cell number and maturational status, different markers [Vimentin, anti-Müllerian hormone (AMH), and cytokeratin-18 (CK18)] were evaluated in healthy and CAO-affected testes at mRNA and protein levels. Sertoli cell number was reduced in CAO-affected dogs. Sertoli cells also partly returned to an immature status, as indicated by the expression of AMH and CK18 at mRNA and protein levels. The degree of spermatogenesis disruption matched with the degree of Sertoli cell alterations. The investigation of CAO in this study is limited by the number of samples and the lack of testicular volume measurements, but this does not diminish its importance in new findings. In conclusion, this study identifies alterations in Sertoli cell number and maturation status as a cause or consequence of CAO. The results indicate the need to restore Sertoli cell function as a potential therapeutic target for a successful restart of spermatogenesis.